Academic Language Development and Linguistic Discrimination: Perspectives from Internationally Educated Students - Page, Christina (Comparative and International Education / Éducation comparée et internationale, 2023)
Language use within Canadian postsecondary institutions reflects ongoing neocolonialism and the privileging of European and North American English varieties. This article shares student perspectives of interactions with faculty on themes of language development and linguistic discrimination, discovered in qualitative interviews using Appreciative Inquiry methodology. Participants’ stories reveal both appreciation for supportive practices that facilitate the development of academic language skills and frustration with linguistic discrimination. Practices valued by participants include using simple and clear language, creating a comfortable environment for non-native English speakers, honouring multilingualism, and providing supportive instruction in discipline-specific language. Students also identified experiences of linguistic discrimination that resulted in academic and personal harm. In students’ stories, a tension between encouraging academic language development while avoiding discriminatory practices emerges. Paths forward in navigating this tension while challenging colonial language hierarchies may include integrating pedagogies using an academic literacies framework while also creating space for translingual practices in classrooms and institutions.